The American Institute for Roman Culture (2003)
[Dt.:] Die Organisation wurde im Jahr 2002 gegründet mit dem Ziel, das kulturelle Erbe Roms zu erhalten. Dazu gehören neben Roms Architektur allgemein auch die archäologischen Denkmäler. Auf der Liste der Tätigkeiten stehen diverse Projekte, darunter Bildungsprogramme, Ausstellungen, Grabungen und Publikationen. - [Engl.:] The organisation was founded in 2002 to promote and defend the cultural heritage of Rome. Next to the buildings of modern Rome in general the archaeological monuments belong to this kind of heritage. The institute carries out cultural heritage projects and organizes a variety of education programs, exhibits, publications and other scholarly activities.